Prevalence of obesity, diabetes and hypertension in immigrant populations in northeastern Mexico - Gómez-Morales, Guillermo Baudelio; Rosas-Torres, Brenda Sofía; Hernández-Jiménez, Williams Jesús; Mattenberger-Cantú, Estefanía; Vargas-Villarreal, Javier; Almanza-Reyes, Horacio; González-Salazar, Francisco (Frontiers in Public Health, 2024)
Introduction Hispanic immigrants are a fast-growing population in the United States of America (USA) that disproportionately suffer from chronic diseases. Despite the increasing prevalence of obesity in Latin-American countries, only a few studies have examined the onset of chronic diseases in Mexican and Central American migrants in Mexico. Objective The objective of this study is to determine the prevalence of obesity, diabetes, and hypertension in Central American immigrants who are in the process of traveling through northeastern Mexico to the United States. Methods An observational, descriptive, cross-sectional study was conducted among migrants, mostly Central Americans. Migrants who agreed to participate in the study were interviewed face-to-face by researchers to obtain their sociodemographic data. To obtain the prevalence, many health indicators related to obesity, diabetes, and hypertension, including weight, height, fasting glucose, and blood pressure, were measured. Results In total, 520 migrants were interviewed; sociodemographic data indicated that most participants were men (76%), from Honduras (72.6%), single (61.2%), and have elementary level of education (48.6%). The somatometric evaluation revealed that 28.9% were diagnosed as overweight, 10.7% with obesity, and 3.3% with malnutrition. Of less prevalence, 8.8% were detected with hypertension and 4.6% had fasting hyperglycemia. The mean participant age was 29.11 ± 10.00 years. For each participant, the average weight was 66.72 ± 13.09 kg; the average height was 1.64 ± 0.08 m; the average body mass index (BMI) was 24.59 ± 4.32; the mean systolic and diastolic pressures were 116.26 ± 15.13 and 74 ± 9.65, respectively; and the average glycemia was 100.97 ± 21.99. El Salvador showed the highest proportion of people with diabetes (14.7%). Women who participated in this study had a higher proportion of obesity (23.4%, p = 0.02) and overweight (36.2%) than men (8.4 and 29.2%, respectively). People from Mexico, Nicaragua, and Honduras reported a high prevalence of overweight participants (63.6, 47.4, and 30.7%, respectively), while people from El Salvador and Nicaragua had a high prevalence of obese participants (23.5 and 21.1%, respectively). Conclusion We found significant differences in the rates of obesity, diabetes, and hypertension between groups of Central American migrants and their place of origin, age, educational level, and gender. Our findings highlight the importance of exploring differences within groups of Central American migrants traveling through northeastern Mexico to the United States, which may explain several health indicators.